Optimisation of Response Surface Methodology (Rsm) For Estimation of Broiler Quail’s Basal Diet - Nur Afiqah Ab. Wahab (2019)
The aim of this research was to optimise the utilisation of Response Surface Methodology (RSM) for estimation of basal feed requirement of broiler quail using three sources of ingredients. The sources were Tapioca starch as carbohydrate source, Black Soldier Fly Larvae (BSFL) as protein source and turmeric as immunity booster. The ration of feed formulation was studied by using a standard RSM design called a central composite design (CCD). It is well suited for fitting a linear surface, which usually works well for process optimisation. The Design-Expert Software Version 7.0 was used to estimate the feed requirement for broiler quail by insert the three factors and Japanese quail was used in this research. A total of 120 quails age 1 day were allocated in 20 cages replicates each with six quails and were given different treatment in each 20 cages. The treatment consisted of 20 different feed formulation which follow the predicted experimental data by Design-Expert Software Version 7.0. The feeding trial was done for 14 days. In this study, three responses that were measured during the experiment were Average Daily Gain (ADG), Feed Conversion Ratio (FCR) and Survival Rate (SR). The results indicated that the graph effect of factor towards response shows the increasing of ADG and decreasing of FCR value from 1.43169 g to 1.60831 g and 3.85698 g to 3.12302 g respectively when the percentage of BSFL was increased. As for SR, the value increased from 71.1156 to 78.5844 when the percentage of turmeric was increased. The desirability of the three responses also high as the desirability was 0.861 which was close to d=1. In conclusion, BSFL and turmeric gave the most positive impact towards the three responses compared to tapioca starch.